Does primary medical practitioner involvement with a specialist team improve patient outcomes? A systematic review. - Mitchell, Geoffrey (2002)
Patients with chronic or complex medical or psychiatric conditions are treated by many practioners, including general practitioners (GPs). Formal liaison between primary and specialist is often assumed to offer benefits to patients. The aim of this study was to assess the efficacy of formal liaison of GPs with specialist service providers on patient health outcomes, by conducting a systematic review of the published literature in MEDLINE, EMBASE, PsychINFO, CINAHL and Cochrane Library databases using the following search terms: 'family physician': synonyms of 'patient care planning', 'patient discharge' and 'patient care team'; and synonyms of 'randomised controlled trials'. Seven studies were identified, involving 963 subjects and 899 controls. Most health outcomes were unchanged, although some physical and functional health outcomes were improved by formal liaison between GPs and specialist services, particularly among chronic mental illness patients. Some health outcomes worsened during the intervention. Patient retention rates within treatment programmes improved with GP involvement, as did patient satisfaction. Doctor (GP and specialist) behaviour changed with reports of more rational use of resources and diagnostic tests, improved clinical skills, more frequent use of appropriate treatment strategies, and more frequent clinical behaviours designed to detect disease complications. Cost effectiveness could not be determined. In conclusion, formal liaison between GPs and specialist services leaves most physical health outcomes unchanged, but improves functional outcomes in chronically mentally ill patients. It may confer modest long-term health benefits through improvements in patient concordance with treatment programmes and more effective clinical practice.